2020
DOI: 10.3390/ma13081875
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Model of Polished Stone Value Attenuation in Coarse Aggregate

Abstract: The polished stone value (PSV) of coarse aggregate is closely related to pavement skid resistance and traffic safety. However, the determination of the PSV of coarse aggregate is conventionally a time- and energy-intensive process. To facilitate the test process of PSV in materials selection and pavement design and for the prediction of the service life of aggregate materials in practical service, here a new mathematical model of PSV attenuation in coarse aggregate, which employs a physical polishing process a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…Comparing these results to the criteria developed by the UK Slip Resistance Group [ 2 ], it can be concluded that an SRV ≥ 36, which is taken as an indicator of low slip risk ( Figure 2 ), was achieved in dry conditions by all the tested solutions. The SRV depended on the type of treatment texture [ 21 , 22 ]. The lowest SRV value was obtained for PO with Ra equal to 1.85 μm (60 units), followed by PL with Ra equal to 25.9 μm (77 units) and SZ with Ra equal to 27.1 μm (93 units).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing these results to the criteria developed by the UK Slip Resistance Group [ 2 ], it can be concluded that an SRV ≥ 36, which is taken as an indicator of low slip risk ( Figure 2 ), was achieved in dry conditions by all the tested solutions. The SRV depended on the type of treatment texture [ 21 , 22 ]. The lowest SRV value was obtained for PO with Ra equal to 1.85 μm (60 units), followed by PL with Ra equal to 25.9 μm (77 units) and SZ with Ra equal to 27.1 μm (93 units).…”
Section: Resultsmentioning
confidence: 99%
“…Materials 2021, 14, x FOR PEER REVIEW 8 was achieved in dry conditions by all the tested solutions. The SRV depended on the of treatment texture [21,22]. The lowest SRV value was obtained for PO with Ra equ 1.85 μm (60 units), followed by PL with Ra equal to 25.9 μm (77 units) and SZ wit equal to 27.1 μm (93 units).…”
Section: Slip Resistance Valuementioning
confidence: 95%
“…During the SLM process, titanium powder melted and solidified quickly, which might lead to the generation of finer‐grained structures. Hardness is not a simple physical concept, but a comprehensive index of the mechanical properties of materials, such as elasticity, plasticity, strength, and toughness 37 . The results of this study showed that the SLM group had higher hardness than the casting and milling groups.…”
Section: Discussionmentioning
confidence: 78%
“…It can be seen that after a period of operation, the BPN of the test roads all showed a significant decrease, indicating that their skid resistance had been reduced. With the operation of the test roads, the exposure of the vehicle tires to the aggregates acts as a polishing and abrasion effect on the aggregates of the pavement [ 33 ]. As a result, the abundant texture of the pavement surface was gradually worn away during operation, resulting in a gradual decline in skid resistance.…”
Section: Resultsmentioning
confidence: 99%